Application of the algorithm for finding the outer median of a graph in the problems of determining the reliability of technical systems - Yuri A. Plaksa; Svetlana A. Kurochkina; Nataliya A. Prusova (Моделирование и анализ информационных систем)
The problem of locating a service center for technical systems with known values of failure flows is considered. This problem was solved using the minisum algorithm of graph theory. The dependence of the system availability factor on the average time between failures and the average recovery time of the system elements is obtained. It is shown that the optimal location of the maintenance point is the median of the graph located at one of its vertices.